Caracterización de antenas fotoconductoras en los THz - Escobar Mejía, Andrés Felipe (2017)
This paper describes an experimental model for determining the characterization of a photoconductive antenna in the terahertz band, in order to detect images in this frequency band. The photoconductive antennas consist of a pair of metal electrodes deposited on a semiconductor substrate, e.g., GaAs grown at low temperature, which upon being excited by a ultra-short laser pulse and biased emit signals in the THz band. To characterize and determine its irradiation, a pyroelectric sensor mounted on a rotator with optical precision is used as detector. The results of the measurements and images determined with the experimental set up that is proposed in this work are shown.